Alignment in Physics, Biology and Psychology - Englman, R. (European Journal of Applied Sciences, 2023)
In a variety of phenomena of our experiences we find that these come into existence (only) thanks to the special way that two disparate items (in the broadest term) are coupled together, which coupling leads to the exclusion of the many more possibilities absent the coupling. Instances of this, here termed ”Alignment”, are discussed within a quantal formalism, for the collapse of wave packets in measurements, for the elongation of protein chains in a cell and for the emergence of awareness resulting from and linked to neural action. For the last, a dual Hilbert-space formulation of mental activities leads to the semi-quantitative explanation of R.N. Shepard’s seminal findings for reaction times in recalls.